Solving Goal Programming by Alternative Simplex Method - Dhote, Monali G.; Dhote, Girish M.; Meshram, Akshaykumar (Communications in Mathematics and Applications, 2023)
It is found that the simplex algorithm is immensely used and proficient algorithm ever invented and shown extremely accurate in the formulation of optimization problems. In this paper, an alternative simplex method with some modifications has been used to solve Goal programming problem. This method is a new approach which solve goal programming problem easily and gives improved solution in comparatively less iterations.